Justice, Human Rights and the Persistence of Hunger: A Current Issue in Bioethics and Biolaw in the 21st Century - Arguedas Ramírez, Gabriela (2019)
Presents the state of the art in biolaw, with a focus on biomedicine Gathers contributions by some of the world’s most prominent experts on biolaw and bioethics Considers controversial topics straight from today’s headlines This chapter aims to constitute a contribution that integrates human rights framework with principles of biolaw -especially the principle of vulnerability- in the analysis of the fundamental importance that the right to food has to guarantee a life that is liveable to every human being. The conclusion will be that is necessary ti guarantee and protect the human right to food, taking into account the obligations that States also have under the principle of vulnerability, wich requires governmental actions that may conflict with international trade regulations, such as those established in free trade agreements.